His and hers: Gendered perspectives and story processing in Glaspell´s "A jury of her peers" - Meyers Skredsvig, Kari (Universidad de Costa Rica, 1998)
Trata sobre perspectivas de género y procesos históricos de la obra "A jury of hers peers" de la autora Susan Glaspell's